2016
DOI: 10.17159/sajs.2016/20150442
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of smectite-rich clay soil: Implication for groundwater defluoridation

Abstract: Groundwater is a widely used and affordable source of drinking water in most of the rural areas of South Africa. Several studies have indicated that groundwater in some boreholes in South Africa has a fluoride concentration above the level recommended by the World Health Organization (1.5 mg/L). Fluoride concentrations above the permissible limit (>1.5 mg/L) lead to dental fluorosis, with even higher concentrations leading to skeletal fluorosis. In the present work, we evaluate the application of smectite-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
5
6
0
Order By: Relevance
“…The results correlate with that reported by Mudzielwana et al [23] and Gitari et al [10] who concluded that CEC is independent of pH. Furthermore, it can also be concluded that the CEC of the clay soil is generally moderate compared to the smectite [23] and montromonilite [22,23].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results correlate with that reported by Mudzielwana et al [23] and Gitari et al [10] who concluded that CEC is independent of pH. Furthermore, it can also be concluded that the CEC of the clay soil is generally moderate compared to the smectite [23] and montromonilite [22,23].…”
Section: Resultssupporting
confidence: 89%
“…pH pzc of the activated clay soil evaluated was found to be 6.1 (adsorbent dosage: 1.0 g/50 mL, contact time: 24 h, agitation speed: 250 rpm and 298 K). This value is close to that of smectite rich (pHpzc 6.0) clay reported in [23] and lower than that of a bentonite clay soil (pHpzc 8.2) reported in [10]. pHpzc refers to the pH at which the clay has zero net charges on the surface.…”
Section: Resultssupporting
confidence: 86%
“…Several authors have indicated that total specific area of the clay mineral can be increased through modification to increase their functionality in different areas of application. Hua [27] Fe3+ modified bentonite 188.9 [20] Na-montmorillonite 78 [21] Fe(OH)-montmorillonite 12 [21] Al(OH)-montmorillonite 14 [21] Al3+ modified bentonite 183.3 [22] Mukondeni smectite rich clay soils 79.93 [23] Mixed mukondeni clay soils 137.7 [24] Montmorillonite 91.61 [25] area could be attributed to swelling of bentonite clay during modification. Mishra and Paride [28] also reported increased specific surface area for bentonite pillared with manganese oxides at temperature of 500°C.…”
Section: Specific Surface Areamentioning
confidence: 99%
“…Mudzielwana et al [23] reported the efficiency of Mukondeni smectite rich clay in fluoride removal. They observed that percentage fluoride removal decreases with increasing pH of the solution with about 92% fluoride removal noted at acidic pH of 2.…”
Section: Fluoride Removalmentioning
confidence: 99%
“…6,7 Furthermore, adsorption has proved to be the sustainable method since it uses materials that can be regenerated. Some authors have also identified number of promising adsorbent including acid-activated kaolinite clay soils, 8 La 3+ -modified bentonite, 9 organosmectite, 10 smectite-rich clay soils, 11 Al/Fe oxide-coated diatomaceous earth, 12 mixed Mukondeni clay soils, 13 and MnO 2 -coated bentonite clay. 14 Clay minerals are promising materials for defluoridation of groundwater due to their abundance and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%